Root-supported overdentures associated with temporary immediate prostheses: a case-report - Souza, Batista Victor Eduardo de; Faria, Almeida Daniel Augusto de; Santiago Junior, Joel Ferreira; Gonçales, Verri Ana Caroline; Piza, Pellizzer Eduardo; Verri, Fellippo Ramos [UNESP] (Oral Health And Dental Management, 2014)
Complete denture fabrication can be a treatment challenge for many dentists, especially when the patient has remaining teeth. So, planning for use of clinical alternatives to improve the treatment prognosis and to enable greater comfort to patient must be considered. This case report describes the use of remaining roots to aid in the stability, support and retention of root-supported overdentures. Thus, immediate prostheses were planned for temporary rehabilitation prior to definitive overdentures. The aim of this study was to demonstrate the planning of root-supported overdentures attached with a ball system for retention associated with immediate dentures between the periods of preparation to fabrication of the definitive overdentures. The proposed treatment met the patient's needs such as being able to carry on normal activities during the sequencing of procedures to be performed over a period of time. The treatment had longevity with patient's knowledge about the necessity of oral hygiene and periodic controls.